Graphical representation of a real valued function in the interval where it gives imaginary value - Md. Mizanur Rahman (International Journal of Physical Research, 2023)
We are introduced to the graph of a real valued function . But when values of are imaginary numbers at some points of real axis, we have no graphical representation of the function at those points. This article demonstrates a model where we construct a 3D graph of the function at those points where values of the function are imaginary numbers.